2001
DOI: 10.1210/jcem.86.6.7580
|View full text |Cite
|
Sign up to set email alerts
|

Low Grade Chronic Inflammation in Women with Polycystic Ovarian Syndrome

Abstract: Low grade chronic inflammation as reflected by increased C-reactive protein (CRP) concentrations independently predicts those at risk for coronary heart disease (CHD) and type 2 diabetes. Women with polycystic ovarian syndrome (PCOS) are insulin resistant and have increased risk for CHD and type 2 diabetes, but currently there are no data on markers of inflammation in women with PCOS. Seventeen women with PCOS (defined on the basis of elevated testosterone and oligomenorrhea) and 15 healthy women matched as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
242
4
9

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 511 publications
(297 citation statements)
references
References 26 publications
29
242
4
9
Order By: Relevance
“…On the contrary, we have not found the increased CRP concentrations recently reported in a smaller series of PCOS patients and healthy controls from Scotland [40]. Nevertheless, we have shown that hyperandrogenism is influenced by certain TNF-α, TNFR2 and IL-6 genotypes [14,15,16], supporting that low grade chronic inflammation might influence the pathogenesis of PCOS.…”
Section: Discussioncontrasting
confidence: 81%
“…On the contrary, we have not found the increased CRP concentrations recently reported in a smaller series of PCOS patients and healthy controls from Scotland [40]. Nevertheless, we have shown that hyperandrogenism is influenced by certain TNF-α, TNFR2 and IL-6 genotypes [14,15,16], supporting that low grade chronic inflammation might influence the pathogenesis of PCOS.…”
Section: Discussioncontrasting
confidence: 81%
“…Over past years, a chronic proinflammatory state has been associated with hyperandrogenism and PCOS (2). On the one hand, increased serum C-reactive protein concentrations have been reported in PCOS patients (3). On the other hand, we have shown that common polymorphisms in the genes encoding tumour necrosis factor (TNF)-a, type 2 TNF receptor, interleukin (IL)-6, and the IL-6 signaling molecule gp130 are associated with hyperandrogenism and PCOS, or influence hyperandrogenic phenotypic traits (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…CRP veya IL-6 gibi düşük doz kronik inflamasyonu gösteren belirteçlerin Tip II DM gelişiminin önemli prediktörleri olduğu gösterilmiştir. Bazı çalışmalarda PKOS'lu hastalarda CRP düzeyleri yüksek olarak bulunmuş, bu da PKOS' ta DM riski artışının kronik inflamasyonun tetiklemesi sonucu olabileceği şeklinde yorumlanmıştır [22]. Artmış serum CRP konsantrasyonları, PKOS' ta da sıklıkla görülen obezite ve insulin rezistansı ile de ilişkili bulunmuştur [23,24,25].…”
Section: Bulgularunclassified